Adansonia digitata ameliorates lead-induced memory impairments in rats by reducing glutamate concentration and oxidative stress. Issue 1 (31st December 2022) - S. Otong, Eduitem; Musa, Sunday A.; Danborno, Barnabas; Sambo, Sohnap J.; Dibal, Nathan I.
ABSTRACT: Lead (Pb) is a neurotoxicant that still remains ahealth problem despite many efforts to minimize its levels in the environment., The use of medicinal plants in the treatment of many diseases and different toxic agents has become popular due to their effectiveness and lower costs. The Adansonia digitata L. (AD) fruit is called a super fruit because of its exotic nature and rich nutrient profile with several medicinal and antioxidants - properties. This study was designed to explore the optional protectivity of Adansonia digitata L. fruit pulp aqueous extract against lead-induced memory impairment, oxidative stress and brain damage. Thirty adult male Wistar rats were distributed into five groups: control, Pb 30 mg/kg, AD 250 mg/kg plus Pb, AD 500 mg/kg plus Pb and Succimer 10 mg/kg plus Pb. Administrations were through oral gavage once daily for 42 days. Lead administration caused memory impairment, increased concentration of glutamate in brain and induction of oxidative stress. AD-treated groups protected memory impairment, reduced glutamate concentration, prevented oxidative stress and ameliorated histopathological changes in the brain. It was concluded that Adansonia digitata ameliorates lead-induced memory impairment in Wistar rats by improving the memory index, controlling glutamate concentration, preventing oxidative stress. Graphical abstract: uf0001